Business Models and Patterns of SME internationalization (Case Study of Furniture SMEs in Pasuruan) - Dedy Saputra; Sudarmiatin Sudarmiatin; Imam Mukhlis (International Journal of Economics, Business and Innovation Research, 2023)
Small and Medium Enterprises (SMEs) in the Furniture sector have overcome internationalization barriers. However, research is still scarce, particularly on achieving the Sustainable Development Goals, despite the importance of this sector. The main objective of our research is to explore the basic pattern and speed of internationalization of SMEs in the forestry products (timber) sector, adopting an external perspective and an empirical approach. More specifically, the interaction effect of demand-side innovation and management control systems (MCS) on firms in the industry is examined. A qualitative research design was developed to gain an in-depth understanding of the contextual factors that influence Furniture SMEs in Pasuruan that have gone international, using direct and semi-structured telephone interview methods conducted with three furniture UKM managers who are members of the furniture and arts forum (FORMAKER). ) Pasuruan, Our findings show that Furniture SMEs in Pasuruan also feel that there is strong competition between Furniture SMEs, thus helping the development of collaborative innovation, directing progress to meet consumer demands, by creating trust and confidence and the process of production innovation and business networks